Giant juvenile phyllodes tumour: a case report - Tomas Maciulaitis; Monika Rimdeikaite; Daiva Gudaviciene; Nerijus Jakutis (Frontiers in Surgery)
BackgroundPhyllodes tumours are rare fibroepithelial neoplasms, accounting for less than 1 percent of all breast malignancies, with most cases occurring in women between 40 and 50 years of age. Their occurrence in the paediatric population is highly uncommon, representing less than 10 percent of all phyllodes tumour cases. Due to overlapping clinical and radiological features, these tumours often pose diagnostic challenges, as they are frequently misdiagnosed as fibroadenomas. In younger patients, additional complexities arise from ongoing breast development and the need to minimize long-term aesthetic and functional impact.MethodsA case report was conducted detailing the clinical presentation, imaging findings, histopathological evaluation, and surgical management of a benign phyllodes tumour in a paediatric female patient.ResultsThe patient presented with a rapidly growing breast mass, initially suspected to be a fibroadenoma. Surgical excision was performed, and histopathological examination confirmed a benign phyllodes tumour. There were no postoperative complications or recurrence at follow-up.ConclusionsThis case highlights the diagnostic and therapeutic challenges specific to paediatric phyllodes tumours. Given their rarity and potential for misdiagnosis, surgical excision followed by histological evaluation remains crucial for accurate diagnosis. Although treatment principles are generally aligned with adult protocols, adolescents management must also consider breast development and requires a more nuanced surgical approach. Balancing oncological safety with the preservation of breast contour and function introduces unique complexities in this age group. Reporting such cases contributes to the limited literature on juvenile phyllodes tumours and raises awareness of their distinct clinical considerations.